Carbon storage and root penetration in deep soils under small-farmer land-use systems in the Eastern Amazon region, Brazil - Sommer, R; Denich, M; Vlek, P.L.G (Plant and soil, 2000)
The north-east of Pará state in the Eastern Amazon of Brazil was settled over 100 years ago. Today the region is an agricultural landscape with variously-aged secondary vegetation and fields with annual cultures, plantation crops and pastures. The effect of these different land covers on carbon sequestration as well as on water and nutrient extraction remain subject of debate. Therefore, we assessed the importance of land use on soil carbon stocks by measuring various C fractions and root biomass (0-6 m) in slash-and-burn systems and (semi-) permanent cultures. An extensive root system down to at least 6 m depth was present under various secondary vegetation stands and slashed and burned fields recently taken into cultivation as well as under a primary forest. Shallower rooting patterns were evident under (permanent) oil palm (4.5 m) and (semi-permanent) passion fruit plantations (2.5 m). Carbon storage in soils of traditional slash-and-burn agriculture up to 6 m depth (185 t ha⁻¹) was not significantly lower than under a primary forest (196 t ha⁻¹) but declined significantly under (semi-) permanent cultures (to 146-167 t ha⁻¹). Compared to above-ground C losses, soil C losses due to slash-and-burn agriculture may thus be small. This is an argument for maintaining the secondary vegetation as part of the agricultural land-use system, as the root system of its trees is conserved and thus C is sequestered also at greater depth.